Personality differences between videogame vs. non-videogame consumers using the HEXACO model - Abbasi, A.Z. (Springer, 2022)
This study investigates whether there exist personality differences between consumers of videogames and non-consumers of videogames. This is explored through the HEXACO model, which derives HEXACO scores indicative of a particular personality profile. The model assesses the dimensions of honesty-humility, emotionality, extraversion, agreeableness, conscientiousness, and openness to experience. The investigation utilized a causal-comparative approach to examine personality differences. A sample of 855 teenage students attending private and public institutions in the Perak and Selangor states of Malaysia participated in the study. The sample contained 475 non-videogame consumers and 380 videogame consumers. The study revealed that videogame consumers have a personality profile that is significantly different on agreeableness, extraversion, conscientiousness, and openness to experience compared to non-videogame consumers. Our study is first to utilize the HEXACO model to evaluate personality differences between videogame consumers and non-videogame consumers. Â© 2020, Springer Science+Business Media, LLC, part of Springer Nature.